2020
DOI: 10.3847/1538-4357/abb45c
|View full text |Cite
|
Sign up to set email alerts
|

The Zwicky Transient Facility Census of the Local Universe. I. Systematic Search for Calcium-rich Gap Transients Reveals Three Related Spectroscopic Subclasses

Abstract: Using the Zwicky Transient Facility alert stream, we are conducting a large spectroscopic campaign to construct a complete, volume-limited sample of transients brighter than 20 mag, and coincident within 100″ of galaxies in the Census of the Local Universe catalog. We describe the experiment design and spectroscopic completeness from the first 16 months of operations, which have classified 754 supernovae. We present results from a systematic search for calcium-rich gap transients in the sample of 22 low-lumino… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 174 publications
(368 reference statements)
6
66
0
Order By: Relevance
“…Figure 8 shows the number of novae recovered in the first 17 months of the PGIR survey simulation as a function of the input Galactic rate. Similar to the rate estimation procedure discussed in De et al (2020i), we estimate the bestfit rate and its confidence interval by creating a distribution of the fraction of simulations that produce the observed number of novae (= 11) as a function of the global rate. We fit a skewed normal function to this distribution to estimate a Galactic rate (with 68% confidence intervals)…”
Section: Monte Carlo Rate Estimatementioning
confidence: 99%
“…Figure 8 shows the number of novae recovered in the first 17 months of the PGIR survey simulation as a function of the input Galactic rate. Similar to the rate estimation procedure discussed in De et al (2020i), we estimate the bestfit rate and its confidence interval by creating a distribution of the fraction of simulations that produce the observed number of novae (= 11) as a function of the global rate. We fit a skewed normal function to this distribution to estimate a Galactic rate (with 68% confidence intervals)…”
Section: Monte Carlo Rate Estimatementioning
confidence: 99%
“…Our current sample of Ca-rich SNe offsets is based on the sample from our original characterization study (Perets et al 2010) based on SNe from the LOSS and CCCP surveys, and the additional Ca-rich SNe discovered by the PTF/iPTF (Kasliwal et al 2012;Lunnan et al 2017;De et al 2018), PESSTO (Valenti et al 2014) and ZTF (De et al 2020;Jacobson-Galán et al 2020 surveys. The SNe offsets are taken from these studies, and summarized in Table 1; the cumulative The cumulative offset distributions of sGRBs and Ca-rich supernovae in early-and late-type galaxies.…”
Section: Ca-rich Supernovae Samplementioning
confidence: 99%
“…The majority of Ca-rich SNe were found in old stellar populations in early-type galaxies (e.g. Perets et al 2010;De et al 2020) it was therefore expected that the locations and offsets of such SNe in their host galaxies would follow the old stellar populations in these galaxies. However, many of the SNe both in our original (Perets et al 2010) sample and additional Ca-rich SNe identified later on (Kasliwal et al 2012;De et al 2020) were found at large offsets from their host galaxies (see Table 1 and Fig.…”
Section: The Progenitors Of Ca-rich Supernovaementioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 shows the light curve produced from the PGIR forced photometry pipeline. Point-spread function (PSF) fit photometry is performed, with noise uncertainty at the location of the transient estimated, as described in De et al (2020b), from difference images produced using the ZOGY algorithm (Zackay et al 2016).…”
Section: Gattini 12 μM (J-band) Light Curvementioning
confidence: 99%